2014
DOI: 10.1038/ejcn.2014.181
|View full text |Cite
|
Sign up to set email alerts
|

Multicausal etiology of anemia among women of reproductive age in Vietnam

Abstract: These findings illustrate the complex etiology of anemia and provide a useful framework for designing, targeting and evaluating appropriate strategies for the prevention and control of anemia. Contrary to expectations, iron deficiency accounted for a very small proportion of anemia in Northern Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 37 publications
4
59
0
1
Order By: Relevance
“…Loss to follow-up postconception was also lower (9.6%) and did not differ by treatment group, although there were some differences in baseline characteristics for the final sample of women with birth outcomes compared with those who did not conceive or were missing birth outcomes. Finally, although dietary intake was low for several micronutrients, the interpretation of our findings is also limited by lack of information on the extent of micronutrient deficiencies based on biomarkers besides iron and vitamin A (33).…”
Section: Discussionmentioning
confidence: 65%
“…Loss to follow-up postconception was also lower (9.6%) and did not differ by treatment group, although there were some differences in baseline characteristics for the final sample of women with birth outcomes compared with those who did not conceive or were missing birth outcomes. Finally, although dietary intake was low for several micronutrients, the interpretation of our findings is also limited by lack of information on the extent of micronutrient deficiencies based on biomarkers besides iron and vitamin A (33).…”
Section: Discussionmentioning
confidence: 65%
“…The fight against anemia calls for detection of the issue first and identification of risk factors in different countries and regions. Additionally, due to great improvements in different countries based on their social, economic and cultural differences, the rate of anemia has been decreasing compared to previous years 14-16…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were disparities by income where women in low SES households were at greatest risk for not meeting dietary nutrient requirements. In addition, we have examined factors associated with anemia at baseline in our study population [50] and found that beyond ferritin concentration, being an ethnic minority (-0.24 mg/dL compared with the Kinh ethnic majority), number of children (-0.17) and socioeconomic status (0.09) were directly associated with Hb concentration ( P <0.05). Retinol Binding Protein (RBP- a marker of vitamin A status) was also directly associated with Hb (0.27 mg/dL) and with ferritin (0.09 mg/dL), whereas hookworm infection was indirectly associated with Hb (-0.11) through RBP and ferritin.…”
Section: Discussionmentioning
confidence: 99%